Product Service Systems as A Driver For Business Model Innovation: Lessons Learned from the Manufacturing Industry - Velamuri, Vivek; Bansemir, Bastian; Neyer, Anne-Katrin; Möslein, Kathrin (International Journal of Innovation Management, 2013)
Firms increasingly rely on business model innovation as a means to face challenges of a world in transition. We identify the conscious integration of products and services, i.e., product service systems, as a valuable strategy to radically innovate product-focused business models. Applying an exploratory multiple case study approach, we uncover five distinct kinds of services that specifically help firms to innovate their business model. These are (1) business consulting, (2) comprehensive services, (3) educational services, (4) financing services, and (5) information management services. The influence of these services on three components of business model innovation (value propositions, value chain architectures, and revenue streams) is discussed. In total, our study emphasizes that integrating specific services with products is an important driver for business model innovations. © 2013 Imperial College Pres
WiSo-Import:2015-03-26:4936
Keywords: Business model innovation (BMI); case study research; manufacturing firms; product service systems (PSS)